Indirect Way for the Assay of Captopril Drug in Dosage FormsUsing1,10-Phenanthroline as a Selective Spectrophotometric Agent for Fe(II) Via Homemade CFIA /Merging Zones Technique - Qassim, Bushra B.; Alwan, Ahmed A . (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
A new speed and sensitive batch and merging zones-flow injection analysis spectrophotometric ways for estimation of captopril in a fine material and in pharmaceutical formulations were suggested. The procedure was depended on the  decline of Fe(III) as FeCl3 to Fe(II) by captopril in acetic acid as medium, the produced Fe(II) interplays with 1,10-phenanthroline to compose a soluble orange-red colored product that is determined at maximum wave length of 511nm. The manifold FIA system was able to determine of CPL. with a throughput 51 sample/h. Calibration curves of absorbance against concentration sign of that Beer, s law is submitted to within the concentration scale of 1-45 & 3-200 mÇ¥.L-1 of CPL. with detection limits 0.0962, 0.0157  mg. L-1  and quantification limits  ,0.321  , 0.0524 mg.L-1 of CPL. for batch and CFIA system, respectively . Repeatability (RSD%)  (n=7) were 0.89 and 0.38 for estimation of CPL. with concentration 60 and 130 mg/L .  The suggested procedure was carried out successfully for estimation of CPL. in pharmaceutical preparations, the values of the both procedures were compared with USP procedure.